A survey of US and Canadian hospitals' paediatric massive transfusion protocol policies. Issue 1 (2nd February 2016) - Horst, J.; Leonard, J. C.; Vogel, A.; Jacobs, R.; Spinella, P. C.
SUMMARY: Background: Trauma is the leading cause of death in children >1 year of age, with haemorrhage as the most common cause of medically preventable deaths. While massive transfusion protocols (MTPs) have been investigated and used in adults to reduce death from haemorrhage, there are a paucity of published data on MTP practices and outcomes in children. This study aimed to survey current MTP policies and the frequency of activation at paediatric care centres. Study design and methods: We conducted a survey of MTPs at hospitals in the United States and Canada, including children's general hospitals, children's specialty hospitals and children's units in general hospitals. We collected information on how the MTP is activated, what therapeutics are given, frequency of its use, and how it is audited for compliance. Results: Forty‐six survey responses were analysed. Physician discretion was the most common activation criteria (89%). A majority of sites (78%) targeted a 'high' (≥1 : 2) ratio of plasma to red blood cells (RBC). Fifteen percent of sites use antifibrinolytics in their MTPs. Eighty nine percent of sites have type‐O RBC units and 48% of sites had thawed plasma units stored in an immediately available location. Conclusion: There is a wide variation in MTPs among paediatric hospitals with regard to both activation criteria and products administered. This underscores the need for future prospective studies to determine the most effective resuscitation methods for paediatric populations to improve outcomes and therapeutic safety for massive bleeding.